Genome-wide physical activity interactions in adiposity - A meta-analysis of 200,452 adults - Graff, M.; Scott, R. A.; Justice, A. E.; Young, K. L.; Feitosa, M. F.; Barata, L.; Winkler, T. W.; Chu, A. Y.; Mahajan, A.; Hadley, D.; Xue, L.; Workalemahu, T.; et al. (PLoS GenetPLoS GenetPLoS Genet, 2017)
Physical activity (PA) may modify the genetic effects that give rise to increased risk of obesity. To identify adiposity loci whose effects are modified by PA, we performed genome-wide interaction meta-analyses of BMI and BMI-adjusted waist circumference and waist-hip ratio from up to 200,452 adults of European (n = 180,423) or other ancestry (n = 20,029). We standardized PA by categorizing it into a dichotomous variable where, on average, 23% of participants were categorized as inactive and 77% as physically active. While we replicate the interaction with PA for the strongest known obesity-risk locus in the FTO gene, of which the effect is attenuated by ~30% in physically active individuals compared to inactive individuals, we do not identify additional loci that are sensitive to PA. In additional genome-wide meta-analyses adjusting for PA and interaction with PA, we identify 11 novel adiposity loci, suggesting that accounting for PA or other environmental factors that contribute to variation in adiposity may facilitate gene discovery.
Keywords: *Exercise; Adiposity/*genetics/physiology; Alpha-Ketoglutarate-Dependent Dioxygenase FTO/*genetics; Body Mass Index; Epigenomics; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; Obesity/*genetics/physiopathology; Waist Circumference; Waist-Hip Ratio